Learning to evaluate through that-clauses: Evidence from a longitudinal learner corpus - Man, Deliang; Chau, Meng Huat (Elsevier, 2019)
The language of evaluation in academic writing has been increasingly studied. However, little is known about how students learn to make evaluative meanings. This article reports on a study of evaluative that-clauses based on a longitudinal corpus of 632 argumentative essays by 158 Chinese undergraduate students. The findings of the study show a non-linear trajectory of change in the use of evaluative that-clauses over time. It was found that the proportion of verb that-clauses decreased whereas the proportions of noun that-clauses and adjective that-clauses increased. Further, while the range of the lexical words co-occurring with evaluative that-clauses expanded, the authorial visibility in stance expression decreased. These changes indicate signs of agency and suggest that the development of evaluative language resources is an organic, dynamic process. Overall the study points to the value of developing and exploring longitudinal learner corpora for studying language learning in general and development in evaluative language in particular. Taking an approach to treating learner language in its own right, the study further contributes to a small but growing body of research based on an empowering ideology and to the empirical literature on evaluation and language learning. Implications for writing instruction are considered.